PAREDES DE CONCRETO: A IMPORTÂNCIA DA SUA UTILIZAÇÃO - de Siqueira Nunes Reis, Daniel; dos Santos Braga, Ana Clara; Maria de Siqueira Nunes, Neuza (LINKSCIENCEPLACE, 2026)
Due to the country’s housing deficit, the federal government facilitated credit to meet the demand for home ownership by offering mainly low- and medium-sized enterprises. In the middle of this scenario, the constructive process of concrete walls is now used to serve the market. The present work aims to present a description of the construction process of concrete walls and the importance of their use. The construction process has cost savings that can reach up to 10% and reduction of time of 50% when compared to conventional masonry. The builders, in turn, found in the process a way to build large scale with low cost, high quality and especially short term.